2018
DOI: 10.1161/atvbaha.118.310997
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Vasculature Requires Estrogen Receptor-α Signaling to Protect From Lymphedema

Abstract: Estradiol protection from developing lymphedema is mediated by an activation of its receptor ERα and is antagonized by tamoxifen. These findings reveal a new facet of the estrogen influence in the management of the lymphatic system and provide more evidence that secondary lymphedema is worsened by hormone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 43 publications
7
54
1
1
Order By: Relevance
“…They identified the estrogen receptor α (ERα) as a key player of the lymphatic endothelial function. In agreement with these findings, they highlighted the detrimental role of hormone therapy on the lymphatic system leading to an aggravation of lymphedema [4]. …”
supporting
confidence: 70%
“…They identified the estrogen receptor α (ERα) as a key player of the lymphatic endothelial function. In agreement with these findings, they highlighted the detrimental role of hormone therapy on the lymphatic system leading to an aggravation of lymphedema [4]. …”
supporting
confidence: 70%
“…In addition to its promotion of amyloid-β removal potentially through stimulating IPAD, taxifolin elevated the expression levels of the lymphangiogenic factors LYVE-1 and VEGF-D. Central VEGF-D is necessary for neuronal function and cognition (48), so our findings imply that taxifolin has beneficially affected cognitive function as well as the integrity of the lymphatic vasculature. The mechanisms underlying the taxifolinmediated up-regulation of LYVE-1 and VEGF-D remain unclear; however, a recent study reported that these factors were expressed by estrogen receptor signaling, thereby increasing skin lymphangiogenesis (49). In addition, the estrogen receptor has been reported to function as a receptor for taxifolin (50).…”
Section: Discussionmentioning
confidence: 99%
“…Such lymphatic dysfunction can occur prior to treatments of surgical dissection and/or RT, suggesting that cancer progression, particularly LN metastasis, contributes to lymphatic dysfunction in cancer patients prior to surgery and RT. While there is evidence that chemotherapy may potentially contribute to the development of cancer-acquired LE [66][67][68][69], further longitudinal studies are needed to understand all the contributing factors that can cause lymphatic dysfunction. Nonetheless, recent results in Figure 7 confirm the results of other studies showing subclinical edema measured with bioimpedance of water content in the arms in breast cancer patients prior to first-line treatment [70,71].…”
Section: The Effects Of Metastasis and Cancer Progression On Lymphatimentioning
confidence: 99%